Three-Dimensional Numerical Modeling of a Coastal Highway Bridge under Stokes Waves. (1st November 2021) - Rajabi, Meysam; Heydari, Fahimeh; Ghassemi, Hassan; Ketabdari, Mohammad Javad; Ghafari, Hamidreza
Abstract : This article investigated the effect of structural flexibility on a coastal highway bridge subjected to Stokes waves through a three-dimensional numerical model. Wave-bridge interaction modeling was performed by an FSI model with the coupling of finite element and finite volume methods. An experimental model validated the FSI numerical analysis. Eventually, the overall results of hydrodynamic and structural analyses are presented and discussed. The results illustrate that the structural flexibility significantly increases the initial shock of the wave force on the flexible bridge. In contrast, the fixed bridge tolerates the least forces in the initial shock of the wave force. Then, by adding a wedge-shaped part to the bridge structure, an attempt was made to reduce the initial shock of the wave force to the structure. The results showed the wedge-shaped part with an angle of 30° reduces the initial shock of wave forces down to 50% for horizontal force and 43% for vertical force on the flexible structure.